A retrospective chart review study on the prevalence of extended spectrum β-lactamases producing bacteria among ICU patients in a tertiary care hospital in Saudi Arabia - Yaseen, Taha; Alburayh, Abdullah; Abdulsalim, Suhaj; Al-Rasheedi, Aisha; Rubah, Norah Al; Alharbi, Huda (International Journal Of Community Medicine And Public Health, 2022)
Background: Antimicrobial resistance is a big concern that face the world. Every class of antibiotics agent has a unique resistant mechanism. The dominant mechanism for resistance to the β-lactam antibiotics in gram-negative bacteria is the production of β-lactamase. Extended-spectrum β-lactamases (ESBLs) production is an important mechanism which is responsible for the resistance to the third generation cephalosporins. Methods: This is a retrospective study which was carried out in the intensive care unit department of King Fahad Specialist Hospital (KFSH), Buraydah, Kingdom of Saudi Arabia (KSA) to estimate the prevalence and associated risk factors of Extended-spectrum β-lactamase producing bacteria (ESBL) among Intensive care unit (ICU) patients. Results: Our study showed that K. pneumoniae (50%) and E. coli (24.7%) were the most commonly isolated organisms as well as some high resistance rate to Meropenem and colistin. This rapid increase of resistance and decrease in sensitivity puts health care works at a serious problem and they must take urgent actions to face it. Conclusions: Focusing more on the right use and good practice of antibiotics, such as prescribing and dispensing antibiotics only when they are needed according to the most recent guidelines, is also need of hour.